Physiographic characterization of the Alto Rio Jamanxim Hydrographic Basin, Pará, Brazil - Getulio Teixeira Batista (Revista Ambiente & Água, 2007)
The objective of this work was to outline and to characterize the sub-basins of the Alto Rio Jamanxim hydrographic basin and to code them using the concept of “otto-basins”, as well as to quantify the deforestation area and the increase in roads extension in its drainage area from 1999 to 2005. The work was based on data of river’s and road’s network, digital elevation model (DEM), and four TM/Landsat-5 images from 1999 and 2005. The outline of the boundaries and the hydrologic parameters of the Basin were based on a 1:250,000 DEM. Results have shown that nine sub-basins have been outlined in the study area, coded up to level 5 (otto-basin code system) and identifiers varied from 44291 to 44299. Deforestation by human activities totaled 635km2 (11% of the Basin) up to 1999 and to 1,257km2 up to 2005, therefore, an increase of 622km2 or 98% between these two dates. Regarding the road network, a total extension of 1,685km was mapped up to 1999 and 3,638km up to July 2005 what corresponds to an increase of 116% in road construction inside the basin boundaries in six years.